Motor performance of premature infants according to Alberta Infant Motor Scale: A literature review (Research, Society and Development, 2021)
Introduction: in the last few years, a significant number of premature children have been born in Brazil, associated with this information are the risk conditions of neonatal morbi mortality wich is occurring during the first year of life. The importance of the thought about medical assistance for the premature child during its very first years is essential, and have the purpose of minimizing the social and biological risks and the consequent child development to which the infant is exposed, this shows the relevance in the measuring the motor development of the premature child, with respect to the corrected gestation age. The analysis of previous paper published that used as instrument of evaluation of triage infant motor development Alberta Motor Scale (AIMS) for premature infants. Methodology: It is an article of the type of literature research, whose source comes from: PubMed, SciELO, LILACS and academic Google, there were selected sixteen published papers from the 2010-2021. Sixteen articles were selected for the construction of the current study, of these, ten were chosen for the construction of the current study, in which two axes of discussion emerged: Low socioeconomic conditions and delayed motor development; and the prolonged length of stay in the NICU and motor performance. Conclusion: The results have shown that the Alberta infant Motor Scale (AIMS) is considered as an screening instrument of the gross motor development with reliability in its application to premature babies, also is an evidence of the socioeconomic conditions, as well as the time spent in the UTIN are risk factors for the child motor development.